Pengembangan Perangkat Pembelajaran Trigonometri Model Flipped Classroom untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa - Ardila, Ayudita; Marzal, Jefri; Siburian, Jodion (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The purpose of this research is to produce valid, practical and effective Flipped Classroom-based mathematics learning tools and to improve students' mathematical communication skills. The method used in this research is the Ploom development model. The development of the Plomp model is namely the initial investigation phase, the development phase, and the assessment phase. Learning tools developed in the form of lesson plans, student worksheets and learning videos. The subjects of the field test were students and educators in class X of SMAN 3 Jambi for the 2020-2021 academic year. The research instruments used were instruments at the initial investigation stage, validity test instruments, practicality test instruments and effectiveness test instruments. The results of the validation of the Flipped Classroom-based mathematics learning device were valid in terms of construct and content. The validity values obtained for lesson plans, learning videos, and worksheets are 3.41; 3.17; and 3,4. Flipped Classroom-based math learning tools are practical in terms of implementation and ease of use. The results of the questionnaire analysis of the student's practicality data showed a figure of 81% so that it was categorized as practical from the observation data on the implementation of learning and interviews. The resulting learning devices are effective in improving students' mathematical communication. The results of the final test of students' mathematical communication skills are 77.78% of students who have scored above the KKM.